2017
DOI: 10.1111/gwmr.12208
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation in a Well‐Characterized Fractured Rock DNAPL Source Area

Abstract: A field demonstration was performed at Edwards Air Force Base to assess bioaugmentation for treatment of a well‐characterized tetrachloroethene (PCE) dense nonaqueous phase liquid (DNAPL) source area in fractured rock. Groundwater recirculation was employed to deliver remedial amendments, including bacteria, to facilitate reductive dechlorination and enhance DNAPL dissolution. An active treatment period of 9 months was followed by a 10‐month posttreatment rebound evaluation. Dechlorination daughter products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Tillotson and Borden further showed that dechlorination transformation products such as cis ‐1,2,‐dichloroethene (DCE) and vinyl chloride (VC) often remain at elevated concentrations after treatment. A recent assessment of bioaugmentation in a fractured rock DNAPL source area showed that reductive dechlorination persisted for 10 months following lactate injection and that continued biotransformation of PCE to ethene masked its rebound from the remaining DNAPL sources (Schaefer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Tillotson and Borden further showed that dechlorination transformation products such as cis ‐1,2,‐dichloroethene (DCE) and vinyl chloride (VC) often remain at elevated concentrations after treatment. A recent assessment of bioaugmentation in a fractured rock DNAPL source area showed that reductive dechlorination persisted for 10 months following lactate injection and that continued biotransformation of PCE to ethene masked its rebound from the remaining DNAPL sources (Schaefer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the complex nature of groundwater flow regimes is recognized in many fractured rock environments (NRC 1996;Shapiro et al 2007;Tiedeman et al 2010;NAS 2015), investigations of engineered bioremediation treatments in fractured rock have, for the most part, relied on simplified interpretations of groundwater flow regimes and the geochemistry of water sampled from permeable fractures to evaluate the robustness of treatment methods (Sorenson 2003;Mora et al 2008;Pérez-de-Mora et al 2014;Schaefer et al 2017). In these investigations, concentrations of contaminants drawn from permeable fractures during treatments are used as an indicator of the success of the treatment method, and continued chemical monitoring after the treatments have ended serve as a means of evaluating contaminant rebound that would be indicative of untreated contaminants diffusing out of the rock matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Biostimulation and bioaugmentation are already established for reductive dechlorination, the longest known degradation pathway for chloroethenes [ 20 ]. Numerous application examples with enrichments as well as commercially available cultures prove the efficacy in laboratory and field tests [ [21] , [22] , [23] , [24] ]. Bioaugmentation can stimulate complete dechlorination [ 25 , 26 ] or accelerate degradation processes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%